KESIAPAN MAHAMAHASISWA DALAM MENGHADAPI COVID-19 UNTUK KEBERLANGSUNGAN PROSES PEMBELAJARAN DARING DAN LURING DI STKIP PESISIR SELATAN - Riri Lestari; Alexander Syam (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2021)
This research is motivated by the condition of the COVID-19 pandemic which does not allow teaching and learning activities to take place normally. So that it has an impact on lecturers as educators and students because indirectly the results and targets of learning achievement are not optimal. Evaluation will always be carried out to prioritize health and safety. The Education Office, Provincial or District / City Health Office, together with the Head of the Education Unit will continue to coordinate with the task force to accelerate the handling of COVID-19 to monitor the level of risk for COVID-19 in the regions. This research contains experiences in the form of school readiness steps in facing Covid-19 for the continuity of the online and offline learning process at STKIP Pesisir Selatan. Based on the results obtained during the pandemic, the principal and lecturer council have compiled several programs, namely for schools and for students. The program for schools is to run the Covid-19 SOP and the program for students is to carry out online and offline learning processes regularly.